HEAVY METAL ACCUMULATION IN Ipomoea reptans AND Helianthus annuus. - S.H., Fauziah; W.I, Wan Siti NurHajar; P., Agamuthu (Malaysian Journal of Science, 2011)
Heavy metals contaminations are among the most hazardous environmental pollution due to its ability to resist disintegration in the natural ecosystem. Thus, they pose risk to living organisms as they are persistent in the environment. Reports on the accumulations of heavy metal in edible plants had alarmed many parties that the general public has become more aware on the seriousness of this issue. Bioaccumulation within the food chain poses potential risks of toxicity effects. Thus, it is crucial to conduct appropriate study to analyze the pathway of the heavy metal elements as a measure to understand the behavior of the heavy metal elements. The aim of this paper is to investigate heavy metal accumulation in plant tissue, particularly the leave, stem and root. Ipomoea reptans and Helianthus annuus were selected as the experimental plant species in the study. Spent dry cell or batteries were utilized as the source of heavy metal contamination of which batteries are commonly discarded in the municipal solid waste stream. Results indicated that the accumulation of heavy metals in the two plants were low and below the limit of European Union Standard for edible plants. However, heavy metal in alkaline batteries exposure was found to promote the growth of longer root in both plants as compared to carbon-zinc batteries and the control. Yet, the accumulation of heavy metal in the plants tissues in this study were only monitored for the period based on the maturation of the plants, longer exposure may result with different outcome, that further investigation is deemed necessary. (Keywords: heavy metal, batteries, edible plants, bioaccumulations)